Leadership presence. (HBR emotional intelligence series., 2018)
Many leaders consider "executive presence" a make-or-break factor in high-powered promotions. But what exactly is this elusive quality, and how do you achieve it? This book explains how to build the confidence, calm, control, and decisiveness that the top leaders feel and project out to the world. Whether you're in a hectic meeting or delivering a critical presentation, you'll be inspired to live into your leadership position with new strength.--Provided by publisher.